Impact of inhibitory KIR ligand mismatch and other variables on outcomes following myeloablative posttransplant cyclophosphamide-based T-cell-replete haploidentical bone marrow transplantation - Sarah Kayser; Sarah Kayser; Sarah Kayser; Emilia Salzmann-Manrique; Hubert Serve; Hubert Serve; Hubert Serve; Peter Bader; Peter Bader; Jan-Henning Klusmann; Jan-Henning Klusmann; Jan-Henning Klusmann; et al. (Frontiers in Immunology)
IntroductionPosttransplant cyclophosphamide (PTCy) has revolutionized the landscape of human leukocyte antigen (HLA)-haploidentical hematopoietic cell transplantation (haplo-HCT), providing a pivotal therapeutic option for patients with hematological malignancies who lack an HLA-matched donor.MethodsIn this retrospective analysis involving 54 adult patients undergoing PTCy-based haplo-HCT, we evaluated the impact of inhibitory killer immunoglobulin-like receptor (KIR)/HLA mismatch, alongside patient, donor, and transplant factors, on clinical outcomes within a homogeneous cohort characterized by a myeloablative conditioning regimen and bone marrow graft.ResultsWith a median follow-up of 73.2 months, our findings reveal promising outcomes: 6-year overall survival, relapse-free survival, and graft-versus-host disease (GVHD) and relapse-free survival rates were 63% (95% CI: 51–79), 58% (95% CI: 46–74), and 42% (95% CI: 30–58), respectively. Notably, the cumulative incidence rates of relapse and non-relapse mortality at 6 years post-haplo-HCT were 29% (95% CI: 19–45) and 12% (95% CI: 6–26), respectively. Acute GVHD at day 100 posttransplantation occurred with a cumulative incidence of 33% (95% CI: 22– 49) for grades II–IV and 9% (95% CI: 3–23) for grades III–IV. Furthermore, 41% of patients developed chronic GVHD within 1 year posttransplantation, distributed as follows: 28% mild, 9% moderate, and 4% severe.ConclusionWithin our cohort, several variables were associated with outcomes following PTCy-based haplo-HCT. However, inhibitory KIR/HLA mismatch did not influence these outcomes.